Progressive Muscle Relaxatation Terhadap Kualitas Tidur Dan Kadar Gula Darah Pada Diabetes Di Desa Hulu Wilayah Kerja Puskesmas Pancur Batu Kecamatan Pancur Batu Kabupaten Deli Serdang Tahun 2019 - Magda Siringo-ringo; Pomarida Simbolon (Elisabeth Health Jurnal, 2020)
Introduction..Diabetes erupts relative to the production of insuline deficits which results in an uncontrolled control mechanism of the level of glucose in the body, giving rise to potential complications of hyperglycemia and hypoglycemia. These conditions make diabetic patients diabetes stress, great anxiety dangerous to increase blood glucose levels in the body, this is as a management recommended complementary therapy using progressive Muscle Relaxations .. The purpose of this study was to determine the effect of Progressive Muscle Relaxation on sleep quality and blood glucose levels in diabetMethod. The design of this study was quasi-experimental with pre and post with control groups, for each group consisting of 32 samples with consecutive sampling techniques. Data were analyzed by statistical tests used by the Wilcoxon Sign Range Test and Mann WhitneyU Result. The influence of Progressive Muscle Relaxation on improving sleep quality was very significant there was a difference in intervention 1 in diabets with p = 0.695 (<0.05) and diabetic intervention group p = 0.00 (p = <0.05). and the effect of progressive muscle relaxation on decreasing blood glucose with found differences before and after intervention I in diabetics p = 0.627 (p> 0.05), with differences in intervention group II diabetes p = 0.00 (p <0.05) showed a significant relationshipDuscussion. There is an autogenic relaxation effect on decreasing blood glucose levels in patients with diabetes mellitus type. Suggestions for Diabetes Progressive Muscle Relaxitation can control the prevention of complications of lowering / stabilizing blood glucose levels, because muscle relaxation is a simple, easy, economical implementation, not a special tutorial room, it just needs intention , the spirit of optimism to be healthy happy future. Hopefully, people with diabetes are always active in implementing progressive, regular muscle relaxation. And the efforts to remain obedient to control blood sugar while balanced a healthy balanced diet. For the Development of Health Sciences / Researchers The results of this study are expected to be used as a reference for data information in finding alternative therapies to control diabetes complications. It is suggested that further research the number of samples is greater in knowing the factors causing comorbidities. Other modifications to complement therapy such as combining music therapy, measuring stress levels, depression, examination (ABI), HBA1C examination